Haptic Cues for Balance: Use of a Cane Provides Immediate Body Stabilization - Sozzi, Stefania; Crisafulli, Oscar; Schieppati, Marco (Frontiers in Neuroscience, 2017)
Haptic cues are important for balance. Knowledge of the temporal features of their effect may be crucial for designing neural prostheses. Touching a stable surface with a fingertip reduces body sway in standing subjects eyes closed (EC), and removal of haptic cue reinstates a large sway. Changes in sway occur rapidly on changing haptic conditions. Here, we describe the effects and time-course of stabilization produced by a haptic cue from a walking cane. We intended to confirm that cane use reduces sway, evaluate the effect of vision on stabilization by a cane, and estimate the delay of the changes in sway after addition and withdrawal of haptic input. Seventeen young subjects stood in tandem position on a force platform, with eyes closed or open (EO). They gently lowered the cane onto and lifted it from a second force platform. Sixty trials per direction of haptic shift (Touch→NoTouch, T-NT; NoTouch→Touch, NT-T) and visual condition (EC-EO) were acquired, together with the traces of Centre of foot Pressure (CoP) and force exerted by cane. A reflective marker was positioned on the cane tip and acquired by an optoelectronic device. Cross-correlation analysis was performed between traces of cane tip and CoP displacement. Latencies of changes in sway in the frontal plane EC following T-NT and NT-T haptic shifts were statistically estimated. The CoP oscillations were larger in EC than EO under both T and NT (p<0.001) and larger during NT than T conditions (p<0.001). Haptic-induced effect under EC (NT/T ~1.2) was less effective than that of vision under NT condition (EC/EO ~1.5) (p<0.001). With EO cane had little effect. Cane displacement lagged CoP under both EC and EO. Latencies to changes in CoP oscillations were longer after addition (NT-T, ~1.6 s) than withdrawal (T-NT, ~0.9 s) of haptic input (p<0.001). Data speak in favour of substantial equivalence of haptic information derived from both ‘direct’ fingertip and ‘indirect’ cane-mediated contact. Cane, finger and visual inputs would be similarly integrated in the same neural centres for balance control. Haptic input from a walking aid and its processing time should be considered when designing prostheses for locomotion.